2019
DOI: 10.1302/0301-620x.101b5.bjj-2018-1306.r1
|View full text |Cite
|
Sign up to set email alerts
|

Distraction subtalar arthrodesis for calcaneal malunion

Abstract: Aims We hypothesized that there is no difference in the clinical and radiological outcomes using local bone graft versus iliac graft for subtalar distraction arthrodesis in patients with calcaneal malunion. In addition, using local bone graft negates the donor site morbidity. Patients and Methods We prospectively studied 28 calcaneal malunion patients (the study group) who were managed by subtalar distraction arthrodesis using local calcaneal bone graft. The study group included 16 male and 12 female patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Harvesting and transplanting autogenous bone from the iliac crest is the gold standard for supporting bone healing in non-unions. However, limited autografts are available and are accompanied with high risks during harvest for wound infection and postoperative pain [ 7 ]. Allogenic bone grafts provide a relatively safe alternative over autografts, which have donor-site disadvantages due to their processing in terms of sterilization and storage, which in turn causes losses of osteogenic and osteoinductive capabilities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Harvesting and transplanting autogenous bone from the iliac crest is the gold standard for supporting bone healing in non-unions. However, limited autografts are available and are accompanied with high risks during harvest for wound infection and postoperative pain [ 7 ]. Allogenic bone grafts provide a relatively safe alternative over autografts, which have donor-site disadvantages due to their processing in terms of sterilization and storage, which in turn causes losses of osteogenic and osteoinductive capabilities [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, when Trnka et al [ 16 ] used allograft bone, 4/5 patients developed nonunion at the fusion site. On the other hand, taking the iliac bone or a medial tibial bone graft increases the secondary trauma, causing pain in the donor site in as high as 29% to 38% of the patients [ 17 ]. Myerson et al [ 18 ] pointed out that Carr et al had poor results in 7 out of 14 cases after fusion, mainly due to the decrease in the calcaneal height caused by bone graft resorption.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, there are various options regarding the operative treatment of calcaneal malunion-from relatively simple in situ arthrodesis to more complex combinations with distraction blocks (using different types of transplants and materials) and calcaneal osteotomies for reconstruction of hindfoot anatomy. 7,15,17,20 Although many original studies, as well as metareviews, have been published annually regarding different aspects of the topic, there is some controversy surrounding the effectiveness of in situ arthrodesis. In 2007, Savva and Saxby 22 reported that in situ arthrodesis combined with lateral wall resection can yield good results, regardless of the loss of talocalcaneal height.…”
Section: Discussionmentioning
confidence: 99%